2021
DOI: 10.3171/2020.3.jns191429
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and outcomes of the supercharged end-to-side nerve transfer: a review of preclinical and clinical studies

Abstract: Proximal peripheral nerve injuries often result in poor functional outcomes, chiefly because of the long time period between injury and the reinnervation of distal targets, which leads to muscle and Schwann cell atrophy. The supercharged end-to-side (SETS) nerve transfer is a recent technical innovation that introduces donor axons distally into the side of an injured nerve to rapidly innervate and support end organs while allowing for additional reinnervation after a proximal repair at the injury site.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 62 publications
1
23
0
Order By: Relevance
“…Because most current studies evaluating the outcomes of nerve transfers in humans rely on subjective measurements (such as ROM and Medical Research Council scores), our current understanding of target end-organ recovery after nerve transfer remains largely conjectural. Although previous studies have postulated that nerve transfers are able to regenerate damaged MEPs and restore lost axonal connections 18 , these speculations have largely been based on rodent models 19,20 with no evidence to verify proposed mechanisms in humans. In this case report, our patient offered a unique opportunity to assess the objective structural response of MEPs in the target end-organ muscle after a nerve transfer procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Because most current studies evaluating the outcomes of nerve transfers in humans rely on subjective measurements (such as ROM and Medical Research Council scores), our current understanding of target end-organ recovery after nerve transfer remains largely conjectural. Although previous studies have postulated that nerve transfers are able to regenerate damaged MEPs and restore lost axonal connections 18 , these speculations have largely been based on rodent models 19,20 with no evidence to verify proposed mechanisms in humans. In this case report, our patient offered a unique opportunity to assess the objective structural response of MEPs in the target end-organ muscle after a nerve transfer procedure.…”
Section: Discussionmentioning
confidence: 99%
“…67 Otherwise, reports of poor results attributable to inappropriate patient selection will discourage adoption among surgeons within their social systems and impede future applications in other nerve injuries. 49,61…”
Section: Discussionmentioning
confidence: 99%
“…67 Otherwise, reports of poor results attributable to inappropriate patient selection will discourage adoption among surgeons within their social systems and impede future applications in other nerve injuries. 49,61 Second, educators should consider cognitive theory when deciding what content to include and how to present it. For example, clinical decisionmaking relies on the interplay of two processes: system 1 thinking, which is fast and often subconscious; and system 2 thinking, which is slower and requires conscious effort.…”
Section: Advancing Decision-making For the Supercharge Nerve Transfermentioning
confidence: 99%
“…SETS also induces a second site (the first being the primary repair site) for SC proliferation and upregulation of NGFs. This in turn prevents SC senescence since prolonged periods without axonal contact causes SC atrophy and cause them to lose their ability to maintain the bands of Büngner [ 49 , 50 ]. Preclinical models using histology, immunofluorescence and retrograde labeling, have demonstrated robust axonal regeneration across coaptation sites [ 50 , 51 ].…”
Section: End-to-side Nerve Coaptationmentioning
confidence: 99%
“…This in turn prevents SC senescence since prolonged periods without axonal contact causes SC atrophy and cause them to lose their ability to maintain the bands of Büngner [ 49 , 50 ]. Preclinical models using histology, immunofluorescence and retrograde labeling, have demonstrated robust axonal regeneration across coaptation sites [ 50 , 51 ]. Lieu et al demonstrated that an upregulation of Insulin-like growth factor (IGF-1) and its receptor (IGF-1R) is upregulated after SETS, and are critical for the survival, proliferation, and differentiation of sensory and motor axons [ 52 ].…”
Section: End-to-side Nerve Coaptationmentioning
confidence: 99%